Synthesis and Spectroscopic Characterization of Water-Soluble Fluorescent Ag Nanoclusters - Chengzhi Zheng; Huiping Wang; Lingzhi Liu; Manjun Zhang; Jiangong Liang; Heyou Han (Journal of Analytical Methods in Chemistry)
Water-soluble fluorescent Ag nanoclusters (NCs) were synthesized at room temperature with sodium dodecyl sulfonate (SDS) as a protective agent. The effects of synthetic conditions on the fluorescence properties of Ag NCs were investigated. The results show that the fluorescence intensity of Ag NCs strongly depends on the synthetic conditions, such as the molar ratio of AgNO3 versus SDS and sodium borohydride (NaBH4), the reaction time, and the pH value of the reaction solution. Under the optimum conditions, the as-prepared Ag NCs exist in face-centered-cubic phase with an average size of 2 nm. Fluorescence spectra of Ag NCs show emission peaks at 365 nm for different excitation wavelength. Resonant absorptions are observed at 203 nm and 277 nm in the absorption spectrum, which can be used to establish the electronic levels in the Ag NCs system.